Treatment of Pesticide Residues Bi-Products in Some Iraqi Vegetables - Mahdi, Maad N.; Mohammed, Ahmed J. (Iraqi Journal of Science, 2021)
Application of pesticide on vegetables will protect them from pest injury, but in another hand will hold pesticide residues inside vegetables. These residues have harmful effect against all consumers. Detection about pesticide residues has been carried out for some Iraqi vegetables (tomato, cucumber, eggplant, and zucchini) by using Gas Chromatography/Mass Spectroscopy (GC/MS). (Quick, Easy, Cheap, Effective, Rugged, and Safe) QuEChERS method has been applied for extraction pesticide residues from targeted vegetables. The GC/MS has been carried out before the treatment of residues for distinguish the vegetables that are suffering from hyper concentration in pesticide residues more than maximum residues limits (MRLs). Three kinds of solutions were used in treatment process with different concentrations: tab water, acetic acid, and citric acid. GC/MS analysis that is carried out before treatment reviled the existence of only bi-products belong to imidacloprid and oxamyl pesticides. The active ingredients of both pesticides degraded efficiently and there is no ability to trace them back. Some of the bi-products represent additives add to improve the ability of pesticide in killing pest. GC/MS had been carried out after treatment of samples with tab water, acetic acid, and citric acid to configure if the bi-products that are belong to oxamyl and imidacloprid still exist or disappeared and to evaluate the efficiency of treatment process. The GC/MS showed that treatment with tab water is the most efficient technique for mitigation pesticide residues in vegetables, whereas, treatment with acetic acid less efficient than tab water technique, whereas, treatment with citric acid is the worst technique in mitigation of pesticide residues due to appearance of more than one bi-products compounds in the results of GC/MS after treatment with citric acid.